Glossocardia andamanica (Asteraceae), a new species from Andaman and Nicobar Islands, India - Karthigeyan, Kaliyamurthy; Rasingam, Ladan; Arisdason, Wilson (Phytotaxa, 2019)
Glossocardia andamanica, sp. nov. (Asteraceae), is described from Andaman and Nicobar Islands, India. This new species morphologically most closely resembles the Malesian species, G. calva (Sch.-Bip. ex Miq.) Veldkamp in having 3-foliolate leaves and awned achenes but differs in colour of ray florets and number of lobes in ray-lip and 4-merous disc florets.